IOT And Its Smart Applications: A Schematic Review - Yusuf Perwej; Nikhat Akhtar (AG Volumes, 2022)
Over the last several years, IoT has become one of the most crucial technologies of the 21st century. People, processes, and even things may now communicate seamlessly thanks to embedded technologies that connect everyday items like kitchen appliances and cars to the internet. Low-cost computers, the cloud, big data as well as the mobile technologies allow physical things to share and collect data without the need for human intervention. Computerized systems can monitor, record, and modify every interaction between linked devices in this hyper connected world. The physical as well as digital worlds come together in a unique way. This review lists some of the advanced applications of IoT technology in different aspects of life.